PERSUASIVE LEAFLET PROMOTION MEDIA AND ITS IMPACT ON KIDNEY HEALTH - Prasetyo, Herry; Handoyo; Hartati, Hartati; Indarti DS, Dina (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Kidney health is greatly influenced by lifestyle, especially eating and drinking patterns. Lack of self-awareness in the student group due to practical and economic reasons, health education using persuasive leaflets is very important to be carried out to increase awareness and change healthy living behavior. Research objective: To determine the use of promotional media in the form of persuasive leaflets in increasing compliance with kidney health behavior in students. Method: This study used a pre-experimental design with a one group pretest-post-test approach. The subjects of the study were 45 students at one of the health colleges in the city of Purwokerto. The intervention was in the form of providing persuasive leaflets designed with the principles of visual communication and simple language. Data were analyzed using a paired t-test to see changes before and after the intervention. Research results: There was an increase in compliance with kidney health behavior in the student group where before the intervention there were 21 people to only 5 people after the intervention. The level of correlation based on the paired t-test statistical test obtained a value of 0.64 which means it has a moderate correlation coefficient. The p value = 0.000 <0.005 indicates that there is a significant difference before and after the intervention Conclusion and suggestion: Persuasive leaflet promotion media can influence student behavior to maintain kidney health. Students must continue to maintain healthy living behavior because they can be role models and agents of change in society.